(3ebOeI aj GdJUQjas
(3ChdgG (B:s
(3hHYO abO SCdfi ef dGjSYfi eVGjbJg Cf CdMb HebOeJi ai GdEYQGH ebOeI ai GdJUQja s
(3BNQgG (B:s
(3ade jcJHhG efgG HGdjGA ZjQ Hdi hEdi hYdi hMJi JeJ s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3OcJhQ eMeO ecjI (B_ (3HZOGO (B(306) s
Keywords: (3GdUQas